(untitled) (Journal of Social Sciences Review, 2023)
This study is devoted primarily to the security priorities of the US towards South Asia in the post-Soviet decade of the 1990s. Indeed, the world witnessed the end of Cold war with the demise of Communist USSR. The United States, therefore, nourished more enthusiastically its inherent desire of a ‘New World Order’. For this purpose, South Asia again became a ‘land of desire’ for Washington to consolidate its preponderance in the strategically vital region of Asia. The research, therefore, delves into a decade long post-cold war security environment of South Asia by analyzing the US policies towards India and Pakistan. The study uses a qualitative methodology that includes a systematic review of existing literature and primary sources, including official documents and statements to identify the important factors that have influenced US strategic partnerships in South Asia and concludes that contemporary Indo-US strategic partnership has its roots since the end of cold war.